KEBIJAKAN BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA DALAM PENGENDALIAN LAJU PERTUMBUHAN PENDUDUK DI KOTA MANADO - LASUT, AMELIA; Mandey, Jantje; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract:Controlling population growth rate is an attempt to suppress the human birth rate in order tocreate a society that is in harmony with the natural capacity. Especially for the city of Manado, Manado citypopulation growth each year has increased, with an average growth rate of 1.1%. To suppress the populationgrowth rate, Indonesia enacting Law No. 52 Year 2009 on Population Development and Family Development.Presence of Women Empowerment and Family Planning at national and local levels are expected to control thepopulation growth rate both nationally and locally.This study aims to determine how the policy Women Empowerment and Family Planning Manado incontrolling the rate of population growth in the city of Manado. The method used is a qualitative researchmethod with data collection techniques used is the study of documentation, interviews and observation.The results of this study indicate that the policy of Women Empowerment and Family Planning Manadoin controlling the population growth rate is the implementation of the Family Planning (KB). Policy supportingfactors, among others: the regulatory system, local regulations and rules mayor of Manado, the RegionalGovernment commitment to family planning and the Empowerment of Women designated by maketh revitalizefamily planning programs become part of the Development Plan 2011-2015; Commitment partners who are goodenough to support the policy of Family Planning and Women's Empowerment; Community participation inplanning programs and the Empowerment of Women in Manado City; and competence of employees adequateapparatus. The efforts undertaken include: Mobilizing and empowering the whole community in the programand the Empowerment of Women; Operasion strengthen human resources; Improving the survival and wellbeingof the family; Ensure the availability of contraceptives and service program for all participants; Improvedaccess to information and reproductive health services; Granting Extension and IEC to members of the PKK,public and Religion through the container meetings PKK village in Posyandu, as well as a group meetingactivities to raise family welfare (Generating), group activities of family resilience (BKB, BKR and BKL) by theextension staff planning in the field of the importance for families to the preservation of family planning;Conducting communication and interpersonal counseling (KIP-Counseling) to the EFA are not family planningthrough home visits by KB officers (PKB).Keywords: Population Growth Rate, Women's Empowerment, Family Planning.